On the Origins of the Hijrī Calendar: A Multi-Faceted Perspective Based on the Covenants of the Prophet and Specific Date Verification - Ibrahim Zein (14620036) (2021)
There has been much speculation as to the type of calendar that was used by the pre-Islamic Arabs and the early Muslim community. The Hijrī calendar is said to have been adopted by ‘Umar b. al-Khaṭṭāb during his Caliphate despite evidence suggesting that it was instituted as soon as the Prophet emigrated to Madīnah. In this paper, we argue that a number of competing Arabian calendars existed up until 17 AH/AD 638, after which the Hijrī calendar was adopted as the definitive calendar of the Muslims. We propose that attempts at reconciling dates emanating from different calendars for major events in the Prophet’s life led to miscalculations which subsequently affected the chronology of the sīrah. This study ultimately argues that a purely lunar calendar was used by the pre-Islamic Arabs in parallel to a lunisolar calendar, and that specific dates reported in the covenants of the Prophet and in the historical works could shed new light in reconstructing the chronology of major events in the Prophet’s life. Other Information Published in: Religions License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/rel12010042